Reciprocal mobilities indigeneity and imperialism in an eighteenth-century Philippine borderland - Dizon, Mark (David J. Weber series in the new borderlands history., 2023)
"Throughout the eighteenth century, independent Indigenous people from the borderlands of the Philippines visited the centers of Spanish colonial rule in the archipelago. Their travels are the counternarratives to one-dimensional stories of Spanish conquest of, and Indigenous resistance in, interior frontiers. Indigenous inhabitants on the island of Luzon constantly moved about-visiting allies and launching raids-and thus shaped history in the process. Their mobility allows us to glimpse their agency in colonial interactions in the early modern period. The landscape contains the traces of how they moved as well as how they channeled and impeded mobility in the borderlands. Mark Dizon views the colonial interactions in Philippine borderlands through the lens of reciprocal mobilities. Spanish mobilities of conquests and conversions had their counterpart in Indigenous visits and ambushes. Colonial encounters were not isolated individual events, but rather a connected web of approaches, rebuffs, rapprochements, and dispersals. They took place not only in the exploration of remote forests and mountains but also in conjunction with Indigenous travels to colonial cities like Manila. Indigenous people of the borderlands were not immobile, timeless actors; they created history in their wake as they journeyed through the borderlands and beyond"--